2003
DOI: 10.1200/jco.2003.12.156
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Psychosocial Risk Indicative of Subsequent Resource Use in Families of Newly Diagnosed Pediatric Oncology Patients

Abstract: A brief screening tool (PAT) is valuable in identifying psychosocial risk factors at diagnosis and is predictive of later use of psychosocial resources. As a next step in this research, the development of psychosocial interventions to match family risk level may be an effective and cost-efficient approach to working with families to address their concerns and promote short- and long-term adjustment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(117 citation statements)
references
References 10 publications
9
105
0
3
Order By: Relevance
“…The results of this study show that the profile of respondents was similar to studies involving caregivers and children with cancer, regarding the caregivers' mean age (36 years) (11) and the mean age of the children (9.5 years) (5,18) . The most frequent diagnosis among children was acute lymphoblastic leukemia, in agreement with the Brazilian statistics, followed by retinoblastoma, which contradicts national data in which the second most common neoplasm in children are lymphomas (1,23) .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The results of this study show that the profile of respondents was similar to studies involving caregivers and children with cancer, regarding the caregivers' mean age (36 years) (11) and the mean age of the children (9.5 years) (5,18) . The most frequent diagnosis among children was acute lymphoblastic leukemia, in agreement with the Brazilian statistics, followed by retinoblastoma, which contradicts national data in which the second most common neoplasm in children are lymphomas (1,23) .…”
Section: Discussionsupporting
confidence: 55%
“…The focus of some research has been the evaluation of the impact of childhood cancer in the family (8)(9)(10) , especially in the lives of parents, however these studies have presented controversial results: while some reported good adjustment (11)(12) , others indicate high rates of parental stress (5,13) . For some researchers these discrepant findings may reflect, at least in part, the use of less sensitive methods to analyze the experiences of parents of children with chronic diseases (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial screening tools that identify families at risk for maladaptive coping with a child's medical condition are available. 67 Once the child is sufficiently developed for a psychological assessment of gender identity, such an evaluation must be included in discussions about gender reassignment. Gender identity development begins before the age of 3 years, 68 but the earliest age at which it can be reliably assessed remains unclear.…”
Section: Psychosocial Managementmentioning
confidence: 99%
“…Although not included in this supplement, the research by Kazak et al regarding a way to identify families at risk for doing poorly (introduced at the 2002 conference) is developing apace of the NCCN guidelines and promises to provide a complementary assessment tool for evaluating and identifying for additional intervention the families of childhood cancer survivors. 20,21 In the final two articles in this supplement, the authors describe what it will take for us to translate the current survivorship science into practice and policy. One of the primary reasons for studying survivorship issues-the complex physical, functional, social, emotional, and economic impact of the many diseases we call cancer-is to use the results of this research to evaluate current and inform future efforts to improve the effectiveness of cancer treatments in curing or controlling cancer, while minimizing its human and social costs.…”
mentioning
confidence: 99%